Diagnosis of coccidiosis by Eimeria spp. in free-range chickens using Mini-FLOTAC and McMaster techniques - preliminary results - Lozano, João (2021)
Mini-FLOTAC is emerging as a more sensitive and accurate tool to identify gastrointestinal parasites in faecal samples from domestic animals, in comparison with the McMaster method. However, research regarding its specific application in poultry samples, particularly from free-range chickens, is scarce. The current research aimed to test the use of Mini-FLOTAC for the identification of Eimeria spp. in free-range chickens and compare its results with McMaster. For this study, 40 faecal samples were collected from free-range chickens in a poultry farm located in North-Western Lisbon (Portugal). Each sample was processed with McMaster and Mini-FLOTAC techniques for the detection and count of coccidian Eimeria spp. oocysts. The resulting OPG (oocysts per gram of faeces) data obtained by the two techniques were compared using the Wilcoxon Test and correlated with the Spearman Test, and Mini-FLOTAC’s relative sensitivity was assessed, using a significance level of p<0.05. The average OPG was higher with Mini-FLOTAC and doubled the one obtained using the McMaster method (2669.3 OPG and 1220 OPG, respectively), although these results were not significant. Mini-FLOTAC’s relative sensitivity obtained in this study reached 86% (70.5-95.3%, 95%CI), although this result was not statistically significant. However, correlation of OPG counts between Mini-FLOTAC and McMaster, was significant. These preliminary results suggest the potential interest in the use of Mini-FLOTAC for the diagnosis of coccidiosis by Eimeria spp. in poultry, based on its assessment in a free-range poultry production system.